2018
DOI: 10.1016/j.ejpb.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of lipid-drug conjugates loaded into liposomes

Abstract: Drugs that are neither lipophilic nor suitable for encapsulation via remote loading procedures are generally characterized by low entrapment efficiencies and poor retention in liposomes. One approach to circumvent this problem consists in covalently linking a lipid to the drug molecule in order to permit its insertion into the vesicle membrane. The nature of the conjugated lipid and linker, as well as the composition of the liposomal bilayer were found to have a profound impact on the pharmacokinetic propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 98 publications
1
22
0
Order By: Relevance
“…The high hydrophobicity of LDCs that allows for high drug loading also significantly hinders compound dissolution into aqueous media. However, similar studies that have incorporated LDCs into liposomal membranes demonstrated that these complexes release from the particles by transferring to other lipid membranes upon direct contact . We believe that the mechanism of release of our system relies on drug transfer between the particles, the macrophage lipid membranes, and eventually the lipid membranes of the neighboring cells.…”
Section: Resultssupporting
confidence: 76%
“…The high hydrophobicity of LDCs that allows for high drug loading also significantly hinders compound dissolution into aqueous media. However, similar studies that have incorporated LDCs into liposomal membranes demonstrated that these complexes release from the particles by transferring to other lipid membranes upon direct contact . We believe that the mechanism of release of our system relies on drug transfer between the particles, the macrophage lipid membranes, and eventually the lipid membranes of the neighboring cells.…”
Section: Resultssupporting
confidence: 76%
“…The volume of distribution (V) was calculated to reflect the theoretical volume in which SN38 is evenly distributed after injection. 28 The calculated V for SN38-PA liposomes was significantly smaller than that of CPT-11 injection, indicating that the concentration of active SN38 in plasma circulation was greater after the administration of SN38-PA liposomes. Moreover, the mean plasma area under the curve (AUC 0-24 h ) for SN38 after the administration of SN38-PA liposomes was 7.5-fold higher than that after CPT-11 administration.…”
Section: Pharmacokineticsmentioning
confidence: 89%
“…Alternatively, PS contains a negatively charged phosphate group attached to the serine group, giving it an overall negative charge, mainly due to the low (2.2-3.6) pKa of the carboxyl group within the serine [42]. More recently, there is increased research interest in formulations of lipid-drug (or photosensitizer) conjugates to improve the pharmacokinetics and therapeutic index of liposomal therapeutics [43][44][45][46][47]. Similarly, the incorporation of PEG, a polymeric steric stabilizer, is widely used to increase the blood circulation time of liposomal formulations [48,49].…”
Section: Toxicological Evaluation Of Liposomes and Their Building Blocksmentioning
confidence: 99%